Economic Empowerment of Islamic Boarding Schools: Is It Possible? - Yuni, Ika Darma; Syahriza, Rahmi; Rahma, Tri Inda Fadhila; Sarah, Fitria (Proceeding International Conference on Islamic Economics Community Services (ICIECS), 2024)
Pesantrens is the oldest educational institutions in Indonesia are developing very quickly and becoming more modern. Attention to Pesantrens is growing in the educational aspect but also in the economic sector. Pesantrens are expected to be independent and empower their potential to increase the economy of Pesantrens and society, including the Al Fauzi Fadilah Amal Foundation Tahfidz Qur'an Pesantren. This research aims to determine and analyze forms of community economic empowerment through Pesantrens. This research is qualitative research. Data of research was carried out by means of observation, interviews and documentation. Data was analyzed by means of triangulation, member check, audit partial, and expert opinion. The results of the research show that Pesantrens have carried out empowerment but have focused more on the education sector, namely by providing free learning opportunities to students who are economically disadvantaged. Meanwhile, in the economic sector, Pesantrens have not yet maximized empowerment due to several factors, namely the age of Pesantrens which are still new, the assets owned by Pesantrens are not yet optimal to finance Pesantren operations, the financing network from Bank Indonesia also cannot be accessed properly, strengthening school web applications is also still not optimal